A family of simple benzene 1,3,5-tricarboxamide (BTA) aromatic carboxylic acid hydrogels. - Howe, R; Smalley, A; Guttenplan, A; Doggett, M; Eddleston, MD; Tan, J; Lloyd, G (2013)
We present the characterisation of a hydrogel forming family of benzene 1,3,5-tricarboxamide (BTA) aromatic carboxylic acid derivatives. The simple, easy to synthesise compounds presented here exhibit consistent gel formation at low concentrations through the use of a pH trigger.